2007
DOI: 10.1371/journal.pbio.0050034
|View full text |Cite
|
Sign up to set email alerts
|

System-Driven and Oscillator-Dependent Circadian Transcription in Mice with a Conditionally Active Liver Clock

Abstract: The mammalian circadian timing system consists of a master pacemaker in neurons of the suprachiasmatic nucleus (SCN) and clocks of a similar molecular makeup in most peripheral body cells. Peripheral oscillators are self-sustained and cell autonomous, but they have to be synchronized by the SCN to ensure phase coherence within the organism. In principle, the rhythmic expression of genes in peripheral organs could thus be driven not only by local oscillators, but also by circadian systemic signals. To discrimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

44
557
3
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 605 publications
(614 citation statements)
references
References 51 publications
44
557
3
4
Order By: Relevance
“…A very elegant study by Kornmann and colleagues showed that rhythmic transcription of most genes in the liver depends on functional hepatocyte clocks (Kornmann et al, 2007). However, the transcription of a subset of genes oscillated in a robust fashion independent of a functional liver clock, and this rhythmic transcription appears to have been driven by systemic cues.…”
Section: Synchronization Of the Liver Oscillator By Systemic Timing Cuesmentioning
confidence: 99%
“…A very elegant study by Kornmann and colleagues showed that rhythmic transcription of most genes in the liver depends on functional hepatocyte clocks (Kornmann et al, 2007). However, the transcription of a subset of genes oscillated in a robust fashion independent of a functional liver clock, and this rhythmic transcription appears to have been driven by systemic cues.…”
Section: Synchronization Of the Liver Oscillator By Systemic Timing Cuesmentioning
confidence: 99%
“…The REV-ERBa protein bound to the promoter region of the Bmal1 gene in the phase of transcriptional repression [31]. This specific action of REV-ERBa was exploited to shut down specifically the circadian oscillator in the liver [42]. Inducible overexpression of this nuclear receptor completely abolished Bmal1 expression and consequently the rhythmicity of the circadian oscillator.…”
Section: Disturbing Rhythms Of Micementioning
confidence: 99%
“…Therefore, we cannot fully exclude that post-translational changes that would be specific to certain forebrain oscillators may impair respective binding of the antibodies to PER1 or PER2 used here, preventing immunoreactive signals in those structures. Moreover, in addition to the circadian control of CLOCK-BMAL1 described in the Introduction section, fine-tune regulation of Per1 (e.g., by glucocorticoids; Yamamoto et al, 2005) and Per2 (e.g., by heat shock proteins or acute temperature changes; Kornmann et al, 2007) may also account for differential expression of these genes in various cerebral oscillators. Nevertheless, our data on daily patterns of PER2 expression in the BLA and DG in mice fed ad libitum are consistent with previous results obtained in rats (Lamont et al, 2005;Waddington-Lamont et al, 2007).…”
Section: Circadian Oscillations In the Forebrain Of Mice Fed Ad Libitummentioning
confidence: 99%